2005
DOI: 10.1016/j.ijpara.2005.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus shiquicus n. sp., a taeniid cestode from Tibetan fox and plateau pika in China

Abstract: Elsevier, Xiao, Ning ; Qiu, Jiamin ; Nakao, Minoru ; Li, Tiaoying ; Yang, Wen ; Chen, Xingwang ; Schantz, Peter M ; Craig, Philip S ; Ito, Akira, International Journal for Parasitology, 35(6), 2005, 693-701. authorThe taeniid cestode Echinococcus shiquicus n. sp. Was found from the Tibetan fox Vulpes ferrilata and the plateau pika Ochotona curzoniae in the Qinghai-Tibet plateau region of China. In the adult stage, E. shiquicus from the foxes is morphologically similar to Echinococcus multilocularis. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
137
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(144 citation statements)
references
References 23 publications
3
137
0
4
Order By: Relevance
“…(e.g., either E. multilocularis or E. shiquicus; see above) at select study sites was likely associated with both the distribution of host species and environmental conditions (Table 3 and Table 4). These site-specific prevalence rates suggested that there might be some carnivores, such as foxes, at all study sites with the exceptions of Gyling Lake and Norling Lake, as the life cycle of E. multilocularis and/or E. shiquicus usually involves foxes (Vulpes vulpes in temperate regions, Alopex lagopus in arctic and subarctic regions and Tibetan fox [Vulpes ferrilata]) as definitive hosts (Schantz et al, 1995;Xiao et al, 2005). Hymenolepis nana showed a prevalence pattern similar to that mentioned above for Echinococcus sp.…”
Section: Discussionmentioning
confidence: 97%
“…(e.g., either E. multilocularis or E. shiquicus; see above) at select study sites was likely associated with both the distribution of host species and environmental conditions (Table 3 and Table 4). These site-specific prevalence rates suggested that there might be some carnivores, such as foxes, at all study sites with the exceptions of Gyling Lake and Norling Lake, as the life cycle of E. multilocularis and/or E. shiquicus usually involves foxes (Vulpes vulpes in temperate regions, Alopex lagopus in arctic and subarctic regions and Tibetan fox [Vulpes ferrilata]) as definitive hosts (Schantz et al, 1995;Xiao et al, 2005). Hymenolepis nana showed a prevalence pattern similar to that mentioned above for Echinococcus sp.…”
Section: Discussionmentioning
confidence: 97%
“…Mixed infections of E. multilocularis and E. shiquicus have been found in the Tibetan fox (Vulpes ferrilata) (Jiang et al, 2012) and the plateau pika (Xiao et al, 2006). Importantly, differences in nuclear DNA sequences, as well as mtDNA sequences, have been found in strict sympatry, providing strong evidence for a lack of genetic exchangeability (Xiao et al, 2005). This is supported by small, but consistent differences in adult morphology and by different metacestode structures (alveolar cysts for E. multilocularis and unilocular cysts for E. shiquicus, which are maintained even in coinfections of the same intermediate host (Xiao et al, 2006).…”
Section: Echinococcus Multilocularis and E Shiquicusmentioning
confidence: 99%
“…There may also be undiscovered species, particularly in parts of the world where the parasite fauna has been less well studied than in Europe and North America. Echinococcus shiquicus, for example, was recently described from the Tibetan Plateau (Xiao et al, 2005). Prior to this study, the adult stage of E. shiquicus in Tibetan foxes (Vulpes ferrilata) had been regarded as a different morphological form of E. multilocularis, while the larval stage in the plateau pika (Ochotona curzoniae) was misidentified as E. granulosus (Xiao et al, 2006).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Species under genus Echinococcus are small tapeworms of carnivores with larval (metacestode) stages known as hydatid proliferating asexually in various mammals including humans (Xiao et al, 2005;. Hydatid cyst has a worldwide distribution and has been recognized since ancient times (Gulam et al, 2002).…”
Section: Introductionmentioning
confidence: 99%